The influence of subpixel measurement on digital camera calibration - Galo, Mauricio [UNESP]; Tommaselli, Antonio M.G. [UNESP]; Hasegawa, Júlio K. [UNESP] (My University, 2012)
The aim of this work is to evaluate the influence of point measurements in images, with subpixel accuracy, and its contribution in the calibration of digital cameras. Also, the effect of subpixel measurements in 3D coordinates of check points in the object space will be evaluated. With this purpose, an algorithm that allows subpixel accuracy was implemented for semi-automatic determination of points of interest, based on Fõrstner operator. Experiments were accomplished with a block of images acquired with the multispectral camera DuncanTech MS3100-CIR. The influence of subpixel measurements in the adjustment by Least Square Method (LSM) was evaluated by the comparison of estimated standard deviation of parameters in both situations, with manual measurement (pixel accuracy) and with subpixel estimation. Additionally, the influence of subpixel measurements in the 3D reconstruction was also analyzed. Based on the obtained results, i.e., on the quantification of the standard deviation reduction in the Inner Orientation Parameters (IOP) and also in the relative error of the 3D reconstruction, it was shown that measurements with subpixel accuracy are relevant for some tasks in Photogrammetry, mainly for those in which the metric quality is of great relevance, as Camera Calibration.
Keywords: Camera calibration; Extraction of points with subpixel accuracy; FöRstner operator; Inner Orientation Parameters; Interest operators; 3D coordinates; 3D reconstruction; Check points; Inner orientation; Least square methods; Multi-spectral cameras; Object space; Point measurement; Points of interest; Relative errors; Semi-automatics; Standard deviation; Sub pixels; Subpixel accuracy; Subpixel estimation; Calibration; Digital cameras; Least squares approximations; Statistics; Video cameras; Three dimensional